IMPACT OF DIGITALIZATION OF HEALTH CARE ON THE ECONOMY - BAGDAT BITENOVA (Research Retrieval and Academic Letters, 2023)
The article considers and defines the concept of digitalization and the health system. The main goal of digital transformations has been formulated, the main sub-goals of healthcare digitalization have been identified. The main directions and activities already undertaken or still planned are listed. Their evaluation at the conference was made.